Comparative machining performance of hardened AISI 4340 Steel under dry and minimum quantity lubrication environments. (2018) - Das, Rabin Kumar; Kumar, Ramanuj; Sarkar, Gourab; Sahoo, Saibal; Kumar Sahoo, Ashok; Mishra, Purna Chandra
Abstract: Hard turning using carbide tools coated with various layer of coatings under different machining environments has come up as a novel technique in the field of machining as compared to conventional grinding and being extensively used in manufacturing industry. To attain superior surface quality, longer tool life and high end finished product multilayer coated carbide tool under different cooling technique like MQL which presents a better alternative. To attain better tool life and better surface finish temperature at the cutting zone should be controlled, which could be archived by machining under MQL condition. Therefore an endeavor is being carried out on an elaborate investigation upon various aspects of machinability like tool wear and average surface quality with multilayer coated carbide insert in hard turning of AISI 4340 steel under dry and MQL condition. The detailed experimental investigation revealed that coated carbide tool having multilayer coating generated good surface quality and performed in reach of the recommended level of 1.6 microns under both the environments. It was confirmed that abrasion was the primary wear mechanism under both the machining conditions. Multilayer coated carbide inserts performed well under MQL condition when compared with dry condition. Surface finish was also superior in MQL condition rather than dry. Cutting speed was the most significant process parameter dominating wear on the flank surface and feed rate predominates regarding surface roughness. From this extensive study it was concluded that even at higher cutting speed multilayer coated carbide tool performed better in MQL environment, along with better surface finish as compared to dry environment.